Model Perencanaan Pembelajaran PPKn Berbasis Literasi - Heri Kurnia; Ahmad Nasir Ari Bowo; Nuryati Nuryati (Universitas Pahlawan Tuanku Tambusai, 2021)
These problems have an impact on the unsuccessfulness in learning objectives of Pancasila education and citizenship and low literacy culture. The successful implementation of Pancasila and civics education learning process is influenced by the learning planning process. The purpose of this research is to find a literacy-based on learning planning model for Pancasila and citizenship education that is able to realize the learning objectives of Pancasila and citizenship education. This research uses a qualitative method or case study type approach. The locations of this research are Public Senior High School 1 in Sewon and public vocational school 1 in Bantul Yogyakarta. The techniques and instruments of this research include interviews, documentation and observation. The data collection procedure used technical triangulation and data source triangulation. Data analysis techniques are data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that the literacy-based learning planning model for Pancasila and citizenship education: (1) School policy on the importance of literacy culture. (2) Support and involvement from parties outside the school. (3) The preparation of Pancasila and civics education learning plans by the Pancasila and school citizenship education teacher team and the district-level civics and Pancasila education teacher team (MGMP) includes the preparation of an annual program, semester program, syllabus and learning implementation plan (RPP). Literacy developed includes digital literacy, reading, writing, science and culture.